2008
DOI: 10.1016/j.cognition.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of cooperation in young children

Abstract: Observations and experiments show that human adults preferentially share resources with close relations, with people who have shared with them (reciprocity), and with people who have shared with others (indirect reciprocity). These tendencies are consistent with evolutionary theory but could also reflect the shaping effects of experience or instruction in complex, cooperative and competitive societies. Here we report evidence for these three tendencies in 3.5 year old children, despite their limited experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
453
4
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(513 citation statements)
references
References 23 publications
43
453
4
13
Order By: Relevance
“…What varied across the conditions was whether the experimenter and the child engaged reciprocally, not whether the experimenter showed an intention to provide. Our research also builds on past research showing that preschoolers understand the principle of economic reciprocity and use it to guide their decisions about what others should do (33). Our findings suggest that children will be more likely to act on the principle of economic reciprocity if they have themselves undergone even a simple reciprocal interaction.…”
Section: Discussionmentioning
confidence: 77%
“…What varied across the conditions was whether the experimenter and the child engaged reciprocally, not whether the experimenter showed an intention to provide. Our research also builds on past research showing that preschoolers understand the principle of economic reciprocity and use it to guide their decisions about what others should do (33). Our findings suggest that children will be more likely to act on the principle of economic reciprocity if they have themselves undergone even a simple reciprocal interaction.…”
Section: Discussionmentioning
confidence: 77%
“…From classic work in child development (Piaget, 1932;Damon 1977Damon , 1980 as well as more recent studies (Olson & Spelke, 2008), we know that children as young as 3 years of age are aware of an equal split as a norm for dividing resources. Some researchers (Henrich et al, 2005) point to research on imitative altruism (e.g., Bryan, 1971;Elliot & Vasta, 1970;Presbie & Coiteux, 1971) to argue that children model their altruistic behavior on adult behavior in their cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies report different results depending on the context in which children are observed, the role of adults in the process, and the alternatives children have at their disposal in the test situation. Most straightforward, in thirdparty situations where they must distribute resources among others, children from as young as 3 years show a very strong bias for equal distributions (e.g., Frydman & Bryant, 1988;Olson & Spelke, 2008;Peterson, Peterson, & McDonald, 1975;Rochat et al, 2009;Shaw & Olson, 2012). When young children themselves are among the recipients, however, the situation becomes more complicated.…”
Section: Introductionmentioning
confidence: 99%